2012
DOI: 10.5194/isprsarchives-xxxviii-1-c22-201-2011
|View full text |Cite
|
Sign up to set email alerts
|

Surveying a Landslide in a Road Embankment Using Unmanned Aerial Vehicle Photogrammetry

Abstract: Commission I, WG I/V KEY WORDS: UAV Photogrammetry, Landslide, Road Embankment ABSTRACT:Most of the works of civil engineering, and some others applications, need to be designed using a basic cartography with a suitable scale to the accuracy and extension of the plot. The Unmanned Aerial Vehicle (UAV) Photogrammetry covers the gap between classical manned aerial photogrammetry and handmade surveying techniques because it works in the close-range domain, combining aerial and terrestrial photogrammetry, but also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 6 publications
1
24
0
2
Order By: Relevance
“…In the last cases, the propagation errors are also taken into account showing values lower than 0.05 m. These errors are of the same order of magnitude than the image resolution, as it has been described in previous comparable studies [26,32,34,38,42,44,45] with similar properties (equipment, flight altitude and resolution).…”
Section: Accuracies Errors and Uncertaintiesmentioning
confidence: 50%
See 2 more Smart Citations
“…In the last cases, the propagation errors are also taken into account showing values lower than 0.05 m. These errors are of the same order of magnitude than the image resolution, as it has been described in previous comparable studies [26,32,34,38,42,44,45] with similar properties (equipment, flight altitude and resolution).…”
Section: Accuracies Errors and Uncertaintiesmentioning
confidence: 50%
“…These studies can be carried out by means of error analysis of the GCPs (error propagation, distribution of points, field GNSS measurements, etc.) as well as the analysis of the resultant products such as DSM/DTMs or orthophotographs [26,28,31,32,34,41,42,45]. Generally, satisfactory results can be achieved, similar to those calculated with conventional aerial photogrammetry [29,44].…”
Section: Introductionmentioning
confidence: 56%
See 1 more Smart Citation
“…Landslide event mapping is a wellknown activity obtained through field surveys (Yoon et al, 2012;Santangelo et al, 2010), visual interpretation of aerial or satellite images (Brardinoni et al, 2003;Ardizzone et al, 2013) and combined analysis of lidar DTM and images (Van Den Eeckhaut et al, 2007;Haneberg et al, 2008;Giordan et al, 2013;Razak et al, 2013;Niculiţa, 2016). The use of RPASs for the identification and mapping of a landslide has been described by several authors (Niethammer et al, , 2010(Niethammer et al, , 2011Rau et al, 2011;Carvajal et al, 2011;Travelletti et al, 2012;Torrero et al, 2015;Casagli et al, 2017). Niethammer et al (2009) and Liu et al (2015) showed how RPASs could be considered a good solution for the acquisition of ultra-high-resolution images with low-cost systems.…”
Section: Landslide Recognitionmentioning
confidence: 99%
“…Current applications of UAS in geomatics can be categorized briefly as follows: agricultural and environmental applications, surveillance, aerial monitoring in engineering, cultural heritage, surveying, and cadastral applications [3]. Particularly, in ground monitoring as a subfield of aerial monitoring in engineering, UAS-based photogrammetry has begun to play an important role in landslide monitoring and detection [4,5].…”
Section: Introductionmentioning
confidence: 99%